Electrical conductivity enhancement of rGO-MoS2 composite electrode for inverted PSC by parameter optimization - Mohd Abid, Mohd Asyadi 'Azam; Safie, Nur Ezyanie; Arith, Faiz; Thangaraj, Joseph Sahaya Anand; Mohamad, Najmiah Radiah; Takasaki, Akito (Elsevier B.V., 2024)
Carbon-based electrodes are widely used in photovoltaic, metal-ion batteries, supercapacitors, and sensors due to their low ohmic resistance and ability to integrate modifiers. Reduced graphene oxide (rGO) represents a promising alternative to graphite in carbon-based electrodes because of its high electrical conductivity, large surface area, and robust mechanical properties. This study aimed to optimize the fabrication parameters of rGOMoS2 composite electrodes prepared via a one-pot hydrothermal method, focusing on maximizing their electrical conductivity for potential electronic applications. Taguchi analysis was employed to evaluate the impact of three key factors: rGO-MoS2 mixing ratio, annealing temperature, and annealing time. The novelty of this work lies in the systematic optimization approach using the Taguchi method, which allowed for the identification of the most significant factors and their optimal levels. The optimal combination was found to be a 1:1 ratio, 75 ◦C annealing temperature, and 15-min annealing time, resulting in an impressive electrical conductivity of 11 800 S m⁻1. This optimized rGO-MoS2 composite electrode exhibited an approximate 11 % reduction in sheet resistance compared to the unoptimized composite. Furthermore, all samples show an improvement in sheet resistance values compared to pure rGO and MoS2, which were 82.5 Ω/sq and 48.9 Ω/sq. Numerical simulations further revealed a 13.23 % improvement in device performance when the optimized rGO-MoS2 composite was implemented as the top electrode in an inverted perovskite solar cell, demonstrating the significant potential of this material for various electronic applications.